Efektivitas Pelatihan Dalam Peningkatan Kemampuan Penyusunan Kebijakan Bagi Aparatur Pengelolaan Keuangan dan Aset Daerah - Tiraina Putri Siregar; Bahrum Jamil; Walid Mustafa Sembiring (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
Training is to improve the knowledge, skills and attitudes of an apparatus so that they can carry out their duties and work well in the study of public administration, namely in policy making. This researcher is in the form of descriptive with a qualitative approach, namely describing the data obtained from the field and explaining it in words. This study aims to describe and analyze how effective the training is to increase the capacity of the apparatus in formulating policies in BPKAD, North Sumatra Province and to identify what factors include obstacles in the implementation of training to increase the capacity of the apparatus in formulating effective policies. The phenomena in this study are the lack of interest of the apparatus in participating in the training, the lack of facilities and infrastructure to support training for effective capacity building of the apparatus in policy making at BPKAD, North Sumatra province.